Do risk perception and safety of sites influence rock climbing destination choices?. (March 2022) - De Salvo, Maria; Grilli, Gianluca; Notaro, Sandra; Signorello, Giovanni
Abstract: The risk of incurring an injury may affect climbers' destination choices for rock climbing, depending on their perceptions about the associated risk and the likely gravity of injuries, and the extent to which they regard the level of protection as a key feature in determining the climbing site's attractiveness. In this study, we conducted a discrete choice experiment and employed a hybrid discrete choice econometric model to investigate whether climbers correctly perceive climbing risks; whether the perceived probability of incurring a slight, severe, or fatal injury affects their choice of climbing site; and whether their preferences for a destination and their risk perceptions are heterogeneous. Further, we estimated monetary preferences for marginal changes in the protection level and when subjective risks equal objective risks. The results indicate a difference between perceived and actual risks in cases of slight or severe injury and a negative relationship between willingness to climb and perceived risk, such that individuals prefer to avoid climbing when perceived risks are high and are willing to pay a reasonable amount for marginal increases in the level of protection of sites. Further, their preferences for site safety are heterogeneous. Management implications: This study highlights critical aspects that need to be considered by natural site managers to prevent accidents and ensure the safety management of outdoor climbing recreation. The main findings are as follows: Actual and perceived risks in rock climbing generally diverge, but with a modality that depends on the type of injury anticipated (i.e., slight, severe, or fatal). On average, climbers underestimate the risk of incurring slight injuries and overestimate the risk of incurring severe injuries. The choice of site at which to climb depends on risk perception, and this relationship (on average) is negative. Further, attitudes to risk decrease with increased stated risks of being slightly, severely, or fatally injured. Across climbers, preferences and risk perception are heterogeneous. Heterogeneity depends on the gender, age, and experience of the climbers. Climbers are willing to take risks. However, they also are willing to pay to reduce risk.